Correlation between Echocardiographic Epicardial Fat Thickness and Angiographic Severity of Coronary Artery Disease - Faroque, Shahid Mohammad Omar; Chowdhury, Abdul Wadud; Ahmed, Mohsin; Sabah, Khandker Md Nurus; Siddiqui, Mohammad Khalilur Rahman; Khuda, Chowdhury Md Kudrat E; Karmaker, Pranob (Bangladesh Heart Journal, 2018)
Background: Epicardial adipose tissue (EAT) is a visceral adipose tissue surrounding the heart and the coronary arteries. Because of its endocrine and paracrine activity, secreting pro-inflammatory and antiinflammatory cytokines and chemokines, it has been suggested to influence coronary atherosclerosis development. Objectives: To identify the relationship between echocardiographic epicardial fat thickness and the extent of coronary artery disease (CAD). Methods: Considering the inclusion and exclusion criteria, a total 87 patients with established or suspected coronary artery disease admitted for coronary angiogram were included in this study. After taking written consent, initial evaluation of the patients was done by history, clinical examination and relevant investigation. Variables, risk factors for CAD and investigation reports were recorded in data sheet. Echocardiography and coronary angiography were done. EAT thickness measurements by echocardiography were compared with coronary angiographic findings. Results: Echocardiographic EAT thickness was significantly higher in patients with CAD in comparison to those with normal coronary arteries 7.14±1.81 mm vs 4.08±1.06mm (p <0.001). Furthermore, EAT thickness increase with the severity of CAD. EAT is 4.08±1.06 mm in patients with normal/non-significant CAD (n=20), 5.75±0.96 mm in single vessel CAD (n=24), 6.54±1.09 mm in double vessel CAD (n=16) and 8.75±1.45 mm in patients with triple vessel CAD (n=27). Conclusions:EAT thickness was significantly higher in patients with angiographically detected CAD in comparison to those with normal coronary arteries. Furthermore, EAT thickness increased with the severity of CAD; i.e. it was thicker in multivessel coronary artery disease than in single vessel or non-significant coronary artery disease. Bangladesh Heart Journal 2018; 33(1) : 47-53